Life after loss: The contributions of logotherapy in the process of overcoming death (Research, Society and Development, 2023)
Life after loss brings great reflections, having variations in not only material/physical but also symbolic spheres, making it possible to conjecture that such losses are also part of the overcoming process, considering that in some way it no longer belongs to the subject. This work was based on the studies of Viktor Emil Frankl, who was the founder of logotherapy, which is considered a psychotherapeutic approach that focuses on the search for the meaning of life as the main human motivator. Given this, logotherapy portrays grief as the result of learning, making it necessary to direct meaning to the experience in order to seek the meaning of life. In this scenario, the methodology was to carry out bibliographical research, aiming at understanding and interpreting the subject's social and cultural phenomena, with the objective of making the work valuable in different fields of study, through the texts that were nourished by the authors regarding the theme. Considerable results are also presented in relation to the research carried out, in which it was possible to observe that, addressing grief is understanding the process as inherent to the human being. It is possible to reflect that the authors presented propose the grieving process as linear, in which they are presented as a process that occurs fluently, passing from one stage to another. This study made it possible to conclude that the precepts of logotherapy presented during the work, which provided clarification and greater definition when it comes to grief and suffering.